PERBANDINGAN PENGARUH INTERBANK OFERED RATE TERHADAP INDEKS SYARIAH DI INDONESIA DAN MALAYSIA - Anantatur, Tatang (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
This study aimed to determine the correlation of interbank offered rate against Islamic stock index associated with behavioral perspective of inves-tors in the stock market of sharia in each country and to examine whether there is a significant difference between the index of sharia that are in Indo-nesia and Malaysia. This study uses an analytical tool that is by simple line-ar regression statistical test to measure the level of effect between variables partially, with a focus on the two countries, Indonesia and Malaysia in the period 2010-2012. Research outcome of the average monthly on secondary data between period 2010-2012, reveals that in Indonesia, independent vari-able affected significantly to Shariah index JII ( Jakarta Islamic Index ) , but there is a difference, compared with Malaysia that the interbank offered rate did not significantly affect KLSI (Kuala Lumpur Sharia Index).Keywords : Interbank Offered Rate, JII dan KLSI.